The Impact Of Cigarette Smoke Exposure On Pathways of Microbial-Induced Pulmonary Inflammation - Gaschler, Gordon J. (My University, 2009)
The cellular, molecular, and genetic mechanisms underlying the pathogenesis of Chronic Obstructive Pulmonary Disease (COPD) are not well understood. The purpose of this thesis was to address the hypothesis that microbial infection is important for the development and/or progression of COPD through investigation of how cigarette smoke alters the response to a bacterial challenge in a mouse model of cigarette smoke-exposure. To this end, in chapter 2 of this thesis we tested the hypothesis that cigarette smoke-exposure attenuates the ability of alveolar macrophages to sense microbial antigens through innate pattern recognition receptors. The central point of this study was the observation that alveolar macrophages isolated from cigarette smoke-exposed mice had attenuated expression of typical inflammatory cytokines following microbial stimulation. Building on this main observation, in chapter 3 we questioned what the consequences of this would be to an in vivo bacterial challenge with nontypeable Haemophilus influenzae. We demonstrated that cigarette smoke-exposure resulted in chronic inflammation, this inflammation was exacerbated following bacterial challenge, and perhaps most importantly, the nature of the inflammatory response was altered. Interestingly, an observation from the study in chapter 3 indicated that exacerbated inflammation in cigarette smoke-exposed mice may be beneficial for clearance of the bacteria, but may come at the expense of damage to the lungs. Consequently, in chapter 4 we questioned the strain and dose/ frequency stringencies of cigarette smoke-exposure on the observation of accelerated bacterial clearance. We demonstrated a role for antibodies in bacterial clearance. Collectively, this thesis provides insight into our understanding of COPD by demonstrating that cigarette smoke-exposure alters the pulmonary immune/ inflammatory response to a microbial challenge, which has a detrimental impact on the lungs.
Impact Of Smoke On Microbial-Induced Pulmonary Inflammation
Keywords: cellular; molecular; genetic mechanisms; pathogenesis; Chronic Obstructive Pulmonary Disease; COPD; microbial infection; cigarette; smoke; exposure; alveolar macrophages; antigens; cytokines